Development of animal model, vaccines, and diagnostics for Schmallenberg virus - Endalew, Abaineh Dagne (Kansas State University, 2019)
Schmallenberg virus (SBV) is a novel orthobunyavirus in the Simbu serogroup, genus Orthobunyavirus, family Peribunyaviridae, and order Bunyavirales. The virus emerged in late 2011 near the German/Dutch border region and was mostly associated with a mild transient disease of sheep and cattle. It is transmitted by biting midges (Culicoides species) and causes abortions, stillbirths, and congenital defects in naïve pregnant sheep and cattle. SBV has spread throughout most of Europe. However, to date, the initial introduction route of the virus to Europe is poorly understood. Consequently, SBV poses a threat to other countries like the US, where competent insect vector species and susceptible livestock populations exist and extensive trade with Europe is conducted. To this end, research work was conducted with the following three aims: (1) development of a large animal model for SBV infection; (2) subunit vaccine development for SBV; and (3) development and evaluation of Schmallenberg disease diagnostics. This dissertation contains four chapters. The first chapter provides a literature review on SBV emergence, taxonomy, replication, transmission, pathogenesis, diagnosis, and control. The remaining three chapters contain the research conducted to address the above-mentioned three study aims. In chapter two, the clinical, virological, and serological responses in two ruminant models, i.e., cattle and sheep, are presented. Infectious serum was shown to be the best inoculum in both species when compared to infectious cell culture supernatant and brain homogenate. The virological and serological responses to SBV were more apparent in cattle than in sheep. Thus, cattle are recommended as the better SBV infection model for the evaluation of vaccines and diagnostics. Chapter three presents the immunogenicity and efficacy of a baculovirus-expressed subunit vaccine composed of SBV glycoproteins C and N. After vaccination, SBV Gc-specific antibody response was detected in all vaccinated animals. Neither of the vaccines conferred protection against SBV challenge infection. Therefore, future studies should focus on better understanding of the difference in post-translational modifications on Gc protein in different expression systems and subsequent conformational and stability conditions that are crucial for its immunogenicity. Using the different reagents (sera, recombinant proteins, and tissues) generated in the SBV animal model development and vaccine experiments, we tried to develop and evaluate serological and molecular diagnostic assays for SBV. Among the different SBV proteins evaluated for SBV antibody detection, N and Gc were the most reactive antigens, followed by Gn. In the indirect ELISA experiments, the SBV-infected cell lysate was the least reactive. Among the three commercial nucleic acid extraction kits, the GeneReach total RNA extraction kit yielded approximately 10× more SBV in vitro transcribed RNA than the Qiagen and Applied Biosystems extraction kits. Multiplex RT-qPCR using in vitro transcribed SBV RNA resulted in favorable amplification of the L and M genes than the S gene. In order to facilitate full genome sequencing of SBV isolates for diagnostic purposes, we established a full genome sequencing approach for three different SBV isolates: FLI-serum, KSU-serum, and KSU-serum cell passaged, using Next Generation Sequencing. Overall, SBV genomes between each of the tested samples have over 99.9% homology, indicating a low level of molecular evolution at this level of investigation. Overall, these studies have highlighted (i) that cattle is the preferred animal model to evaluate SBV vaccines and diagnostics, (ii) the need for identifying the right protein expression system that ensures proper conformation and stability and, finally, (iii) that both M and L segment PCRs are more specific than the S segment PCR, which is relevant especially in areas where other Simbu serogroup viruses are endemic.
Keywords: Schmallenberg virus; Animal model; Ruminants; Vaccines; Diagnostics